Suitability of wheat (Triticum aestivum) varieties for dual purpose under varying seed rate and fertilizer levels - HARENDER; HOODA, V S; RAJ, DEV; MAL, TODAR; DEVI, SUDESH; AKSHIT (The Indian Journal of Agricultural Sciences, 2022)
To meet the demand of grain and fodder, dual purpose crops can be a good alternative that can also reduce burden on the land. A field study was carried out during two consecutive rabi seasons of 2017–18 and 2018–19 on research farm of Agronomy, CCS HAU, Hisar, Haryana, to evaluate the performance of dual purpose wheat (Triticum aestivum L.). The experiment was laid out in split plot design with three replications. It comprised two varieties (C 306 and WH 1105) along with cut management in main plots, and two seed rates (100 kg/ha and 125 kg/ha) with three levels of fertilizer, viz. RDF, 115% of RDF and 130% of RDF in sub-plots. The findings revealed that significantly higher crop growth rate (CGR) up to 60 DAS was observed in C 306 over WH 1105, whereas, after 60 DAS, higher CGR was observed in WH 1105 over C 306. Maximum tillers/m2, dry matter accumulation, effective tillers, grain and biological yield, crude protein were obtained in WH 1105 without cut, closely followed by C 306 without cut. Among, seed and fertilizer rate combinations, significantly higher CGR, protein and crude protein content other growth parameters were observed in 125 kg/ha seed rate +130% RDF and 100 kg/ha seed rate + 130% RDF. It was concluded that C 306 may be a good choice for dual purpose wheat which can provide fodder in lean period without affecting its yield if supplied with slightly higher dose of fertilizers